Fermentative maceration time influences chromatic and phenolic composition of wines elaborate with the 'Bordô' grape (Revista de Ciências Agroveterinárias, 2024)
The aim of this study was to evaluate the effect of different fermentation maceration periods on the physicochemical, chromatic, and phenolic composition of wines made from the 'Bordô' vine. This work was carried out at the Fruit Growing Laboratory of the Federal Institute of Santa Catarina - Canoinhas Campus, in 2022. The 'Bordô' grape was harvested from a commercial vineyard, totaling five treatments consisting of different fermentation maceration periods: 02, 04, 06, 08 and 10 days. The wine was bottled in July 2022, after malolactic fermentation had finished, and the wines were evaluated ten days later. The analyses were carried out in triplicate, evaluating relative density, pH, total acidity, color intensity, color tone and total polyphenols. The data was submitted to analysis of variance and the means were compared using the Tukey test. The fermentation maceration period did not influence the color tone, total titratable acidity, relative density, and pH of the wines. In terms of total polyphenol content and color intensity, there was an increase in these variables as a function of the length of fermentation maceration. Therefore, the length of fermentation maceration influences the color and phenolic composition of wines made from the 'Bordô' grape.
Keywords: Vitis labrusca L.; total polyphenols; color intensity; color shade